resolva
2x + y = 4
14x - 3y = 3
x + y = 2
(3x + 2y = 6
Soluções para a tarefa
Respondido por
1
Resposta:
1- 2 x + y- 4 = 0
( 2 ) ⋅ x + ( y- 4 ) = 0
x =- ( y- 4 )2
x = -12y+ 2
2- 14 x - 3 y- 3 = 0
( 14 ) ⋅ x + ( - 3 y- 3 ) = 0
x =- ( - 3 anos- 3 )14
x =314y+314
3- x + y- 2 = 0
( 1 ) ⋅ x + ( y- 2 ) = 0
x =- ( y- 2 )1
x = - y+ 2
4- 3 x + 2 y- 6 = 0
( 3 ) ⋅ x + ( 2 y- 6 ) = 0
x =- ( 2 anos- 6 )3
x = -23y+ 2
Perguntas interessantes
Filosofia,
9 meses atrás
Ed. Física,
9 meses atrás
Geografia,
11 meses atrás
Matemática,
11 meses atrás
Biologia,
1 ano atrás
Português,
1 ano atrás